Neurocognitive changes associated with concussion in elite cricket players are distinct from changes due to post-match with no head impact. Issue 5 (May 2021) - Goh, Sherwin C; Saw, Anna E; Kountouris, Alex; Orchard, John W; Saw, Richard
Abstract: Objectives: Determine intra-individual changes in CogSport performance in elite cricket players diagnosed with concussion, and differentiate this from changes which may be attributed to post-match with no head impact. Design: Retrospective observational study of elite Australian male and female cricket players with diagnosed concussion and prospective cohort study of cricket players with no head impact post-match. Methods: CogSport performance relative to an individual's baseline was compared between 46 cricket players diagnosed with concussion following a head impact sustained during a match, and 84 cricket players who played a match during which they had no head impact. Results: CogSport performance post-match for players diagnosed with concussion was slower for detection speed (p < 0.001), identification speed (p = 0.007), and one back speed (p = 0.011). No changes in one card learning speed or any accuracy measures were observed. CogSport performance post-match with no head impact was faster but less accurate for one card learning (both p < 0.001). No changes in the other three test components were observed. Conclusions: Slower performance in three of four CogSport tasks (detection, identification, one back) may be indicative of concussion, as these intra-individual changes were not observed in players post-match with no head impact. The fourth task, one card learning, may not be a useful indicator of concussion as it was not observed to change with concussion yet was susceptible to change post-match with no head impact. CogSport may have clinical utility in assisting the clinical diagnosis of concussion in elite male and female cricket players.